2006
DOI: 10.1021/jp0613081
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio and Density Functional Theory Reinvestigation of Gas-Phase Sulfuric Acid Monohydrate and Ammonium Hydrogen Sulfate

Abstract: We have calculated the thermochemical parameters for the reactions H 2 SO 4 + H 2 O T H 2 SO 4 ‚H 2 O and H 2 -SO 4 + NH 3 T H 2 SO 4 ‚NH 3 using the B3LYP and PW91 functionals, MP2 perturbation theory and four different basis sets. Different methods and basis sets yield very different results with respect to, for example, the reaction free energies. A large part, but not all, of these differences are caused by basis set superposition error (BSSE), which is on the order of 1-3 kcal mol -1 for most method/basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
105
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 42 publications
13
105
1
Order By: Relevance
“…The most stable isomers (within 2 kcal mole í1 of the most stable isomer/global minimum) obtained at the PW91PW91/6-31+G* level have been optimized using the PW91PW91/6-311+G(3df,3pd) method to obtain the final results. The choice of the computational method is based on the satisfactory performance of the PW91PW91 [46] on atmospheric clusters, including predicting the Gibbs free energies, structural characteristics and vibrational spectra in a very good agreement with experiments and ab initio studies, and availability of large amount of data for different atmospheric species/clusters computed at PW91PW91/6-311+G(3df,3pd) level of theory for comparison [24][25][26][27][28][29][30]34]. The availability of data for ternary sulfuric acid-water-ammonia clusters computed at the same level of theory is a very important factor because the assessment of different nucleation pathways, which is based on the analysis of the reaction free energies computed using the same method, is clearly more legitimate than that based on the comparison of results obtained at different levels of theory [47].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most stable isomers (within 2 kcal mole í1 of the most stable isomer/global minimum) obtained at the PW91PW91/6-31+G* level have been optimized using the PW91PW91/6-311+G(3df,3pd) method to obtain the final results. The choice of the computational method is based on the satisfactory performance of the PW91PW91 [46] on atmospheric clusters, including predicting the Gibbs free energies, structural characteristics and vibrational spectra in a very good agreement with experiments and ab initio studies, and availability of large amount of data for different atmospheric species/clusters computed at PW91PW91/6-311+G(3df,3pd) level of theory for comparison [24][25][26][27][28][29][30]34]. The availability of data for ternary sulfuric acid-water-ammonia clusters computed at the same level of theory is a very important factor because the assessment of different nucleation pathways, which is based on the analysis of the reaction free energies computed using the same method, is clearly more legitimate than that based on the comparison of results obtained at different levels of theory [47].…”
Section: Methodsmentioning
confidence: 99%
“…The ability of computational quantum chemical methods to provide an adequate description of molecular interactions in nucleating vapours has been pointed out in Nadykto et al [24], in which the classical problem of the ion sign preference established in back 1897 by Wilson [1] has been solved. Recently, computational chemical studies of atmospheric species have become a focus of intense activity [24][25][26][27][28][29][30][31][32][33][34][35][36]. Although a large number of the computational quantum studies considering atmospheric clusters has been published within the last five years, only a few are dedicated to the interaction of common organics with atmospheric nucleation precursors [32,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Along the trajectory several cluster structures were extracted, the geometry was optimized, and frequencies were calculated. The lowest identified molecular structure of the ( 5 cluster is shown in Figure 5 calculated using the M06-2X functional.…”
Section: Cluster Formationmentioning
confidence: 99%
“…An error analysis study by Kurtén et al [66] found that the B3LYP density functional underestimates the binding energy of sulfuric acid-water and sulfuric acid-ammonia clusters compared to high-level coupled-cluster methods. The underestimation of B3LYP binding energies for sulfuric acid-water was also noted by Al Natsheh et al [55] and Nadykto and Yu [67].…”
Section: The Role Of Ammonia In Water-sulfuric Acid Nucleationmentioning
confidence: 99%
“…Even computational methods with relatively large systematic errors can thus yield useful and reliable data, as long as the errors are constant for the set of systems compared. For example, a test comparison [66] of 12 computational methods (3 theories and 4 basis sets, with and without counterpoise corrections) yielded differences as large as 5 kcal/mol for the absolute value of the binding energy of the H 2 SO 4 ·NH 3 cluster, but all predicted values within about 2 kcal/mol from each other for the difference in binding energies of the H 2 SO 4 ·NH 3 and H 2 SO 4 ·H 2 O clusters. The latter value, as discussed in [38] and [68] is much more important for assessing the role of ammonia in sulfuric acidwater nucleation.…”
Section: Studies On Clusters Containing Other Molecular Speciesmentioning
confidence: 99%